2015
DOI: 10.1210/jc.2014-4462
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MKRN3 Levels Decline Prior to Pubertal Onset and Through Puberty: A Longitudinal Study of Healthy Girls

Abstract: Declining levels of circulating MKRN3 preceded pubertal onset. The negative correlation between MKRN3 and gonadotropins further supports MKRN3 as a major regulator of hypothalamic GnRH secretion during childhood. Undetectable or low MKRN3 levels were observed in a subgroup of patients with early onset of puberty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
42
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 27 publications
10
42
4
2
Order By: Relevance
“…These findings are in agreement with the results of the recent study in girls (5). In boys, however, the change in MKRN3 levels appears biphasic with a rapid decline prior to clinical onset of puberty and slower changes thereafter once puberty progresses, whereas in girls, the decline in serum MKRN3 continued to mid-puberty (5).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are in agreement with the results of the recent study in girls (5). In boys, however, the change in MKRN3 levels appears biphasic with a rapid decline prior to clinical onset of puberty and slower changes thereafter once puberty progresses, whereas in girls, the decline in serum MKRN3 continued to mid-puberty (5).…”
Section: Discussionsupporting
confidence: 92%
“…There are currently two publications on circulating MKRN3 levels in humans (5,6,7). In girls, MKRN3 levels declined before the onset of puberty and correlated negatively with increasing gonadotropin levels (5), which further underpins the potential role of MKRN3 in the central inhibitory control of puberty. In adult men, circulating MKRN3 levels did not seem to reflect the integrity of the hypothalamic-pituitary-gonadal (HPG) axis (6,7), as the levels were similar in men with hypogonadal or normal testosterone levels.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent genome wide-association study identified two single-nucleotide polymorphisms of MKRN3 significantly associated with an older age at menarche only when inherited from the father (19). These SNPs were not associated with serum MKRN3 concentration (18), but they might be associated with a persistence of intracellular MKRN3 activity for a longer period of time after birth than for the WT allele (18).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the MKRN3 protein inhibits GnRH secretion in mice (11). A recent study on a large group of healthy Danish girls showed that serum MKRN3 concentration declined before the onset of puberty and was lower in a subset of girls with early puberty onset than in the subset of age-matched prepubertal girls (18). A recent genome wide-association study identified two single-nucleotide polymorphisms of MKRN3 significantly associated with an older age at menarche only when inherited from the father (19).…”
Section: Discussionmentioning
confidence: 99%